Elio Vittorini and the 'Eliot affair' in the journals «Politecnico» and «Sud» (Prassi Ecdotiche della Modernità Letteraria, 2022)
This paper aims to show how, in the years immediately following the Second Word War, two politically-committed journals, «Politecnico» and «Sud», edited, respectively, by Elio Vittorini and Pasquale Prunas, published translations (by Raffaele La Capria and Tommaso Giglio) of the second and fourth of T.S. Eliot’s Four Quartets that subjected the poet’s work to a form of ideological appropriation which seems to be imputable to Vittorini himself.
Keywords: Il Politecnico; Sud; Thomas Stearns Eliot; Elio Vittorini; Raffaele La Capria; Tommaso Giglio; translation; ideological appropriation